Las aves y la limnología - Martínez, Mariano M. (1991)
Birds areone ofthe most conspicuous faunal components of aquatic environments. They participate, directly or indirectly, in the general dynamics of these ecosystems. The most outstanding roles played by birds are, among others: (1) Consumers at different levels ofthe trophic chain. (2) Suppliers of organic matter; this influence, whilestill poorly understood, is of much significance at both roosting sites of gregarious species (gulls, herons, ibises, etc.), and at nesting colonies. (3) Transport and interchange of material among di.fferent aquatic and terrestrial environments. (4) Birds modify the environment, they cut and accumulate importan! amounts of aquatic macrophytes during the reproducti ve season and bioturbate the sediments during feeding process and the locomotion. (5) Casual transportation of living organisms from different ecosystems and distant geographic areas. On the basis of the above aspects and taking into account their size, relative abundance and the time spent in these environments, birds are significant participants in their ecological dynamics. However, in most handbooks on limnology, the role of birds and their importance are neglected, being generally considered as foreign or occasional faunistic components.